2018
DOI: 10.1136/tobaccocontrol-2018-054470
|View full text |Cite
|
Sign up to set email alerts
|

Young adult susceptible non-smokers’ and smokers’ responses to capsule cigarettes

Abstract: BackgroundFlavour capsule cigarette variants (FCVs), which allow users to customise their smoking experience and reduce the harshness of smoking, have captured an increasing share of many markets. We examined tobacco companies’ argument that such product innovations aim simply to shift market share, by estimating smokers’ and susceptible non-smokers’ responses to FCVs.MethodsWe conducted an online survey of 425 smokers (daily and non-daily), susceptible non-smokers (n=224) and former smokers (n=166) aged betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 36 publications
1
49
1
Order By: Relevance
“…22 In fact, prior evidence has shown that young adults who are non-smokers are more likely to initiate the use of flavored e-cigarettes. 56 In this study, stratification by conventional cigarette smoking status demonstrated that ever use of e-cigarettes was higher among the younger adult age groups of 18 to 34 years and 35 to 54 years when compared with participants aged ≥55 years for both smokers and non-smokers of conventional cigarettes.…”
Section: Discussionmentioning
confidence: 57%
“…22 In fact, prior evidence has shown that young adults who are non-smokers are more likely to initiate the use of flavored e-cigarettes. 56 In this study, stratification by conventional cigarette smoking status demonstrated that ever use of e-cigarettes was higher among the younger adult age groups of 18 to 34 years and 35 to 54 years when compared with participants aged ≥55 years for both smokers and non-smokers of conventional cigarettes.…”
Section: Discussionmentioning
confidence: 57%
“…Other work suggests that RYO is a lower cost alternative to smokers who may otherwise quit and so this may explain the introduction of more RYO offerings in lower price segments 40–42. Similarly, menthol and particularly flavour-capsule variants appeal more to non-smokers and non-daily smokers compared with smokers and may therefore recruit non-smokers 8. Flavoured cigarettes including capsule flavourings will be outlawed in the EU by May 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously companies reduced the total number of brands sold and renewed their focus on value for money brands by increasing the number and length of cigarettes in a pack and introducing menthol variants in this price range 6. In response to standardised packaging in New Zealand and other markets there has been a significant increase in flavour capsule variants (FCVs) across all market price points,7 which may threaten standardised packaging’s effect on deterring smoking initiation given that these products appeal more to non-smokers and non-daily smokers than to daily smokers 8 9…”
Section: Introductionmentioning
confidence: 99%
“…While limited research has been conducted on perceptions of flavor capsule cigarettes, early research has found that among youth flavor capsule cigarettes are perceived as less harmful and are associated with greater attractiveness and interest to try 17-19 . Young adults also have positive perceptions of flavor capsule cigarettes 20,21 . Adult smokers in the UK have reported using them because of the taste, smoothness, choice of flavors, and enjoyment associated with bursting the capsule 22 .…”
Section: Introductionmentioning
confidence: 99%